2010
DOI: 10.1136/adc.2009.197699
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal drug exposure and renal function in very preterm infants

Abstract: Among all drugs described as nephrotoxic in very preterm infants, ibuprofen alone proved to be nephrotoxic in this study for a 1-month span follow-up. If GFR is lower than the median reference value on day 7 after ibuprofen infusion, physicians should keep in mind that glomerular clearance of drugs may stay decreased for the first month of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
(43 reference statements)
0
18
0
1
Order By: Relevance
“…The lower GFR in infants administered ibuprofen persisted for the month of follow-up. Importantly, aminoglycoside serum concentrations were higher in infants receiving ibuprofen, suggesting potentially enhanced toxicity [151]. Exposure to aminoglycosides was not associated with a lower GFR in this study although 7 days could be too soon to detect an effect.…”
Section: Introduction To a Health Problemmentioning
confidence: 72%
See 2 more Smart Citations
“…The lower GFR in infants administered ibuprofen persisted for the month of follow-up. Importantly, aminoglycoside serum concentrations were higher in infants receiving ibuprofen, suggesting potentially enhanced toxicity [151]. Exposure to aminoglycosides was not associated with a lower GFR in this study although 7 days could be too soon to detect an effect.…”
Section: Introduction To a Health Problemmentioning
confidence: 72%
“…Tocolytic therapy administered to the mother until the day of delivery was significantly associated with a lower GFR in the infant on day 7, and administration of the COX-2 inhibitor nimusulide as a tocolytic has been reported to induce renal failure and ESKD in neonates in multiple case reports [151,155,156]. In animals, multiple medications that could be prescribed during pregnancy have been found to impact offspring kidney development, including β-lactam antibiotics, cyclosporine, and long-term steroids, although their renal impact in humans is largely not known and long-term follow-up is needed [48,65,157].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these potential nephrotoxic insults, other possible treatment options might be considered for treatment of a PDA. However, the only other medical option for closure of the PDA is ibuprofen, which is also shown to injure glomeruli in a neonatal animal model and has been shown to affect glomerular filtration rate (GFR) during the first month of life in human studies [12,29,30]. Judicious use of these medications during the neonatal period is warranted and should be balanced with the clinical condition of the neonate and the severity of the PDA.…”
Section: Discussionmentioning
confidence: 97%
“…Indomethacin was shown to have more significant suppressive effects than ibuprofen on renal COX-2 and vasodilator prostanoids in a neonatal rat model (26). Ibuprofen has been shown in premature neonates to result in a low glomerular filtration rate for a month following administration (60). A recent study has shown increased numbers of podocytes in the urine of preterm neonates receiving indomethacin, suggesting drug-induced glomerular injury at the time of ongoing glomerulogenesis (31).…”
mentioning
confidence: 99%